Critical Discourse Analysis of Oprah Winfery Speech at the 2018 Golden Globe - Maryam Mowafaq Abed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
This paper seeks to analyze the potential of change in Oprah winfrey's speech at 2018 Golden Globe using the critical discourse analysis framework presented in Norman Fairclough's 1992 publication Discourse and Social Change. The model is reflected in the “three dimensional method of discourse analysis; Text analysis, discursive practices and Social practices. The research aims to identify linguistic strategies as well as discursive strategies and how they are conducted by Oprah and what are the social practices in which the discourse acquires its potentials for change. The study has concluded that Oprah use of the strategies was not of the manipulating type, because she is calling for conscious awaken change for all the woman around the world and not for personal interest .the research showed that Oprah employed the linguistic level in a way that back up the strategy of presenting her personal experience as a model to be inspired..